OP0089 EFFICACY OF CLOMIPRAMINE FOR CHRONIC LUMBAR RADICULAR PAIN A RANDOMIZED CLINICAL TRIAL. (2nd June 2020) - Afilal, S.; Fellous, S.; Ilham, A.; Abouqal, R.; Hmamouchi, I.; Alami, N.; Latifa, T.; Rkain, H.; Allali, F.
Abstract : Background: Lumbar radicular pain is the most common chronic neuropathic pain syndrome. Antidepressants are highly recommended for neuropathic pain, but there is no evidence for their efficacy. Objectives: The aim of this double-blind, randomised, placebo-controlled trial is to determine whether Clomipramine (an antidepressant) is more effective than placebo in reducing pain in individuals with resistant chronic lumbar radicular pain. Methods: A double-blind, randomized, clinical trial. Sixty-two patients with resistant chronic lumbar radicular pain were included. (The sample size was calculated on the assumption that clomipramine would reduce the incidence of lumbar radicular pain of 35%, compared with placebo, with a two-sided test, an alpha level of 0.05, and a power of 85%). Patients were randomly allocated to receive either Clomipramine by slow intravenous infusion for 10 days in a hospital setting with progressively increasing doses, 25 mg on the first day, 50 mg on the second day and 75 mg on the third day until the tenth day, or placebo (500 ml of physiological serum a day). For both groups, paracetamol is added intravenously at a dose of 3g per day for ten days, Parecoxib for 3 days and ten sessions of lumbar spine rehabilitation including analgesic massage, muscle strengthening and joint maintenance. At the exit, clomipramine was relayed with 25 mg per day orally until the 90th day for clomipramine group, and paracetamol was authorized in both groups, in case of severe pain. The primary outcome was pain intensity, measured at baseline, 5th day, 10th day and 90th day using VAS pain (10 mm). Secondary outcome included DN4-questionnaire, lumbar radicular discomfort (VAS 10 mm), pain-free perimeter of walking (min), disability assessed using the Roland Morris Disability questionnaire and severity of mood symptoms assessed using the Hospital Anxiety and Depression scale (HAD), measured on days 0, 5, 10 and 90. Results: 31 patients were assigned to the clomipramine group and 31 to the placebo group. There were no differences between the groups in demographic characteristics. Treatment by Clomipramine had a significantly greater reduction in pain, discomfort and DN4 from the 5 th day (p = 0.000, p = 0.001 and p = 0.004 respectively) than the placebo, with an improvement maintained until 90th day. There was a statistically significant improvement in pain-free walking distance and disability for the clomipramine group from the 10 th day (p = 0.02 and 0.001 respectively) and that maintained until 90 th day. However, there was no significant improvement in HAD between the 2 groups. (p ≥ 0.1). Conclusion: This double-blind, randomized, clinical trial shows that clomipramine is quickly effective and maintained over time in the management of resistant chronic lumbar radicular pain. It can therefore be part of the therapeutic arsenal in this sense. Disclosure of Interests: None declared